Silymarin: A Historical and Scientific Exploration of its Medicinal Properties - Shivaprasad, Hebbani Nagarajappa; Gharabude, Vinaya; Thimmannagari, Sravani; Krishnamani, Madhu; Soni, Gaurav (Pharmacognosy Reviews)
Silybum marianum, or milk thistle, has been used medicinally for over 2,000 years, mainly to treat liver conditions. Silymarin, a complex mixture of flavonolignans, is present in the plant, which contributes to its pharmacological properties. Silymarin, especially its active compound silybin used particularly for liver health. This review compiles information from databases such as Google Scholar, PubMed, ScienceDirect, and ResearchGate. It is used in traditional medicine to treat liver conditions like cirrhosis and hepatitis, promoting regeneration, reducing oxidative stress, and enhancing detoxification. It also boosts glutathione levels, lowers liver fibrosis, and has been shown to protect the liver from a number of toxins, including alcohol and environmental pollutants. Various research studies confirm its safety with no serious side effects and it has been proven fairly low in toxicity. Further validating its role as a promising therapeutic agent for liver diseases.
Keywords: Milk thisle; Hepatoprotective; Silymarin; Pharmacology; Herbal medicine